Dietary Exposure of Japanese Quail (Coturnix japonica) to Perfluorooctane Sulfonate (PFOS) and a Legacy Aqueous Film‐Forming Foam (AFFF) Containing PFOS: Effects on Reproduction and Chick Survivability and Growth. (26th July 2021) - Bursian, Steven J.; Link, Jane E.; McCarty, Michael; Harr, Kendal; Roberts, John; Simcik, Matt F.
Abstract: Effects of perfluorooctane sulfonate (PFOS) and a legacy aqueous film‐forming foam (AFFF) containing 91% PFOS (AFFF PFOS) on reproduction, chick survivability, and growth of Japanese quail ( Coturnix japonica ) were determined. Day‐old Japanese quail were administered PFOS or AFFF PFOS at 6 dietary concentrations ranging from 0 to 21 mg kg –1 feed for a total of 20 wk. At the age of 4 wk, 16 male/female pairs per treatment were assigned to cages, and egg laying was induced by the age of 10 wk. Eggs were collected daily, set weekly, and incubated for 18 d for the following 10 wk. Hatchlings were fed uncontaminated feed for 2 wk and euthanized to collect blood and liver. After 10 wk of egg collection, adults were euthanized to collect blood, liver, and kidneys. Significantly increased myofiber numbers in the liver and glomerular sclerosis in the kidneys of adults indicated damage at greater doses. Perfluorooctane sulfonate or AFFF PFOS did not significantly affect egg production; however, hatchability was decreased at the highest PFOS dose. The no‐observed‐adverse‐effect levels for chick survivability, considered the critical effect, were 4.1 mg PFOS kg feed –1 (0.55 mg kg body wt –1 d –1 ) and 5.0 mg AFFF PFOS kg feed –1 (0.66 mg kg body wt −1 d –1 ), resulting in calculated average toxicity reference values of 0.25 mg kg feed –1 and 0.034 mg kg body weight –1 d –1 . Environ Toxicol Chem 2021;40:2521–2537. © 2020 SETAC